Protecting public welfare regulation through joint treaty party control: a ChAFTA innovation - Anthea Roberts; Richard Braddock (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2016)
The recent FTA between China and Australia aims to protect public welfare measures through joint treaty party control. This Perspective assesses the FTA's mechanism in the context of broader efforts to rebalance investor protection and state sovereignty, and to recalibrate interpretive authority between arbitral tribunals and treaty parties.
Keywords: 330